ISSUES OF INTELLECTUAL PROPERTY PROTECTION IN INTERNATIONAL TECHNOLOGY TRANSFER (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the challenges and complexities surrounding intellectual property protection in international technology transfer. It analyses the various issues that arise when transferring technology across borders, including differences in legal frameworks, enforcement mechanisms, and cultural attitudes towards intellectual property. Additionally, the article examines the role of multinational corporations, governments, and international organisations in addressing these challenges and promoting innovation and cooperation in the global marketplace.